Pengaruh Self Worth Terhadap Hasil Belajar Matematika - Ribaah, Robisha Zarifa; Yullah, Ahmad Sofi (FARABI: Jurnal Matematika dan Pendidikan Matematika, 2024)
Self  worth is the internal sense of being good enough and worthy of love and belonging from others. In this study, we will analyze self-worth affected mathematic learning outcome classes IXF at MTs Mambaul Huda Krasak. Whic is self worth as independent variable and mathematic learning outcome as dependent variable. Questionnaire of self-worth scala, documentation, interviews, and observations is data collection technique in this quantitative methods study. analysis prerequisite test results show that the significance value of the linearity test on self-worth scale questionnaire results and  mathematic learning outcome was 0,56 > 0,05, it indicates that the data was linear. the significance value of the person correlations was 0,000 < 0,05, it indicates that there was a positive and significant. The results show that the higher the students' self- worth, the higher the students' mathematic learning outcome. It implies that there was an influence between self worth on mathematic learning outcome.